A percepção dos profissionais que atuam na rede de assistência social em relação à vivência de rua de crianças e adolescentes - Witt, Cibele dos Santos (2016)
The present study reason about the perception of professionals who act in the three complexity levels of the Sistema Único da Assistência Social (SUAS), concerning the streetlife experience of teenagers and children.. Seeking to identify how these professionals perceive the movement between the exit from home and the permanency on the streets and the implications of this dynamic on the constitution of the subjectivity of teenagers and children. Also, seeking to know if in the perception of these professionals the public politics of social protection, especially the ones focused on homeless people, contemplate the phenomena of streetlife experience of teenagers and children. Aiming at reach such goals a qualitative study with exploratory character with psychologists and social workers professionals was performed. A semistructured interview was used as a tool, it occurred from three guiding principles: 1) homelessness and family relations; 2) homelessness and subjectivity and 3) homelessness and public politics of social protection for people in homelessness situation. The data were analyzed through thematic content analysis and the research results will be presented and discussed in two articles which compose this thesis. The first article discusses the delicate embrittlement of the family bonds and the streetlife experience of teenagers and children, a category which emerged from the first guiding principle. On this article the aspects which gained prominence in relation to the reasons that lead teenagers and children to leave their houses and seek the streets as a survival alternative, namely: intrafamily violence, drugs abuse and poverty, are approached. The second article discusses three categories which emerged from the second and third guiding principles, namely: liberty and friendship; protective relations through groups formation; and the place of public politics in between the exit from home and the street permanency. The importance of public politics of social protection to childhood and youth as being an important instrument to professionals who act in the Sistema de Garantia de Direitos, especially of the Sistema Único da Assistência Social on its three levels of complexity: CRAS, CREAS e Acolhimento Institucional was emphasized. Finally, for children and teenagers with street life experience, this territory presents itself as a great paradox, because even exposing them to several danger factors, the street fulfills an important function, since it allows them the construction of meaningful relations that can influence greatly on the process of subjectiveidentity constitution, it was considered according to the point of view of the professionals who compose the study.